MANAJEMEN PEMASARAN JASA PENDIDIKAN BERBASIS BUDAYA RELIGIUS - Afif Alfiyanto (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
In general, this study aims to determine the marketing management of religious culture-based education services at SDIT Luqman Al-Hakim International Yogyakarta. In addition, this study intends to determine the importance of marketing management of religious culture-based education services at SDIT Luqman Al-Hakim International Yogyakarta. This research applied a qualitative field method. The samples were determined using purposive sampling and snowball techniques. The data were collected using interview, observation, and documentation techniques. In this study, the researcher used a descriptive-qualitative data analysis technique with an inductive approach to analyze the data. The results of this study indicated that: (1) SDIT LHI conducts marketing management based on religious culture to fulfill the needs of education customers who will build a generation of Muslims that has strong and noble characters, masters the principles, has scientific basis, contributes to the good of the world, and is devoted to Allah SWT. There are 7 elements used in marketing management, namely: 1) Product, 2) Price; 3) place; 4) Promotion; 5) Human Resource; 6) Physical Evidence; 7) Process. (2) The implementation of religious culture is carried out by school through the dimensions of monotheism, the Shari'ah, and morality contained in the curriculum, vision, mission, school purpose, school programs, and the learning process. (3) Factors that support the marketing of education services at SDIT LHI, which are a. Application of PHI curriculum; b. Competent human resources; c. Complete educational facilities; d. Promotional activities that use many strategies; e. Easily accessible school locations; and f. A lot of achievements in the public and religious fields. Meanwhile, the inhibiting factors are a. The lack of student input due to fairly expensive tuition fees; b. Temporary teaching staff; c. Competition with other educational institutions; d. Marketing management lacks employees; e. Different interpretations of school purposes by school administrators and parents.